Coping with discrimination among HIV-positive Black men who have sex with men. Issue 7 (3rd July 2017) - Bogart, Laura M.; Dale, Sannisha K.; Christian, Jana; Patel, Kinjal; Daffin, Gary K.; Mayer, Kenneth H.; Pantalone, David W.
Abstract: In the USA, HIV-positive Black men who have sex with men show large disparities in disease outcomes compared to other racial/ethnic and risk groups. This study examined the strategies that HIV-positive Black men who have sex with men use to cope with different types of discrimination. A total of 27 HIV-positive Black men who have sex with men participated in semi-structured interviews, which were transcribed verbatim and coded using thematic analysis by multiple raters. Major coping themes included reactive avoidance (using behaviours, cognitions and emotions to escape from discrimination), a common reaction to racism; proactive avoidance (avoiding situations in which discrimination is anticipated), manifested as selective disclosure of HIV-serostatus; external attribution for discrimination (versus self-blame), used more for sexual orientation and HIV discrimination; and social support-seeking, which most often emerged in response to racism. Active coping strategies, such as self-advocacy (countering discrimination directly or indirectly), were infrequently reported. Findings suggest a need for structural anti-discrimination interventions, in tandem with culturally congruent individual- or group-level interventions that aim to enhance men's existing adaptive coping strategies.